Asuhan Kebidanan Komunitas pada Keluarga Tn M dengan Kurang Energi Kalori pada Kehamilan di Dusun Mong Desa Kuta Kecamatan Pujut Kabupaten Lombok Tengah Tahun 2024 - Ismayanti Ismayanti; Elly Sustiyani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study was conducted to observe and implement midwifery care provided to Mrs. M who was 25 weeks pregnant in Dusun Mong, Pujut District, Central Lombok Regency, from June 21 to July 4, 2019. The mother had a history of 4 pregnancies, 2 deliveries and 1 pregnancy. Her pregnancy condition was normal, but she experienced Chronic Energy Deficiency (CED). After receiving PMT supplements in the form of biscuits for 2 weeks, there was an increase in the Upper Arm Circumference (LiLA).